Synopsis of the genus Spigelia (Loganiaceae) in North America, Central America, and the Caribbean - Islas-Hernández, C. Sofia; Alvarado-Cárdenas, Leonardo O. (Instituto de Ecología, A.C., 2023)
Background and Aims: Spigelia is a Neotropical genus with about 90 species distributed from the United States of America to Argentina. The diversity of the genus presents a spatial separation with a group in North-Central America/ the Caribbean (NA) and another in South America (SA), each with an important center of diversification. However, the systematic knowledge of the group has not been updated in the last 10 years, so the objective of this work is to generate a systematic synopsis for the genus distributed in the NA region. Methods: The work was carried out through the search for bibliographic information to obtain the taxonomic history, field work and review of herbarium material, based on which diagnostic descriptions and distribution maps were made. Key results: Twenty-nine species distributed in the NA region were found, which represents about 30% of the diversity of the genus, distributed in the tropical and subtropical zones. In the NA region, Mesoamerica is one of the regions in which plant diversity is concentrated, which classifies it as a hotspot. This work includes novel information on the morphology of the group, such as descriptions of the pollen and carpological characters, identification keys for regions in NA and distribution maps in the study area. Conclusions: This study represents the first taxonomic treatment for the genus Spigelia that includes all the species of the central and northern regions of the Americas. The information collected in this work may be useful to be integrated into phylogenetic analyzes that help resolve the infrageneric relationships of the group. Likewise, the application of potential distribution modeling tools that would allow locating areas for future collection, as well as the development of biogeographic analyzes that help us understand the distribution patterns of Spigelia diversity along the continent.